Everyday desistance: the transition to adulthood among formerly incarcerated youth - Abrams, Laura S. (Critical issues in crime and society, 2017)
Machine generated contents note: Foreword Acknowledgments -- 1 Introduction 2 The Road to Juvie 3 Locked up and Back Again 4 And Now I'm an Adult 5 Dangers and Decisions: Navigating Desistance as a Young Man 6 You Can Run but You Can't Hide 7 Finding a Net to Fall Back On: The Young Women's Journeys 8 Everyday Desistance: Theory Meets Reality 9 Policy and Practice Reforms: Supporting the Pathway to Adulthood -- Appendix Bibliography Index